Queering Two Resistance Novels: Historical Trauma, Open Secrets, and Non-Genealogical Plot in Carlo Coccioli's Il migliore e l'ultimo and Beppe Fenoglio's Il libro di Johnny. Issue 1 (2nd January 2023) - Codebò, Marco
ABSTRACT: A queer reading of Coccioli's Il migliore e l'ultimo and Fenoglio's Il libro di Johnny complicates the narration of the Italian Resistance by following a zig-zag path. This path begins on 8 September 1943, a traumatic day in which the national fiction fell apart, leaving the two novels' heroes stranded without an army, a country, or a king. The path continues through the Resistance in the form of youth secession: the escape of thousands of young women and men away from home to build their own territorial, resistant communities. The last stage in this path consists of the rejection of the vertical link with the father and the establishment of horizontal connections between individuals who until recently were unknown to one another.